The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.20473/jn.v13i1.5690
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Maternal Sensitivity Model as a Strategy to Optimize Family Perception on the Role of Parents and the Growth of Infants

Abstract: Introduction: Family perceptions on the role of parents and the growth of infants must be seriously considered by healthcare workers since they can affect the role of family development in taking care of the babies. A family that has optimally understood the role of their development as a parent will be able to give the appropriate care for the babies.Methods: The study aimed to find out the effects of a family-based Maternal Sensitivity Models (MSM) strategy for family perception optimization on the role of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The previous research stated that the education of nutritionbased effective community improves dietary habit and children' growth [15]. Another research revealed that the education of nutrition-based effective community aimed to optimize children's nutrition in 1000 1 st day of birth improved a mother's intention to actively provide nutritious food [16] and educational program of sensitivity-based effective family improved a mother's perspective to take care of her children [17], [18]. Hence, this study focused on an educational program of nutrition to mothers which were expected to be capable in practicing healthy dietary habit, adapting to new foods to her children, and increasing their self-efficacy to take care of their children with ARFID.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research stated that the education of nutritionbased effective community improves dietary habit and children' growth [15]. Another research revealed that the education of nutrition-based effective community aimed to optimize children's nutrition in 1000 1 st day of birth improved a mother's intention to actively provide nutritious food [16] and educational program of sensitivity-based effective family improved a mother's perspective to take care of her children [17], [18]. Hence, this study focused on an educational program of nutrition to mothers which were expected to be capable in practicing healthy dietary habit, adapting to new foods to her children, and increasing their self-efficacy to take care of their children with ARFID.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research stated that the education of nutrition based effective-community to improve dietary habit and children' growth [14]. Another research revealed that the education of nutrition based effective-community aims at optimizing children's nutrition in 1000 First-Day of Birth (HPK) [15] and educational program of sensitivity based effectivefamily improving mother's perspective to take care of her children [16]. Hence, this study focuses on the education program of nutrition to mother which is expected to be capable of practicing healthy dietary habit, adapting new food to her children, and increasing mother's self-efficacy to take care of children with ARFID.…”
Section: Introductionmentioning
confidence: 99%